Single‐dose rituximab in refractory lupus nephritis. Issue 8 (August 2016) - Kotagiri, P.; Martin, A.; Hughes, P.; Becker, G.; Nicholls, K.
Abstract : Background: Off‐label use of rituximab in lupus nephritis is reported to be beneficial. While the optimal dose is unknown, the regimen of four intravenous doses of 375 mg/m 2 is commonly employed, despite expense and potential side‐effects. Aim: To investigate the response to single‐dose rituximab, added to standard corticosteroids plus additional immunosuppressive agent, in refractory lupus nephritis. Methods: Consecutive consenting patients with refractory lupus nephritis despite steroids plus either cyclophosphamide, mycophenolate or azathioprine were enrolled in this ethics‐approved, open‐label, prospective study. After baseline assessment, patients received one intravenous infusion of 375 mg/m 2 rituximab. Clinical, biochemical and serological (DsDNA, complement) responses to this dose were analysed. Complete renal response (CR) was defined as normalisation of creatinine, albumin, proteinuria and urinary RBCs and partial response (PR) as ≥50% improvement in at least one parameter, without deterioration in others. B‐cell depletion was defined as peripheral CD19 lymphocyte count ≤0.05 × 10 9 /L. Results: Fourteen patients were enrolled in the study. All were B‐cell‐depleted until 8 months post‐dose. Eleven patients (79%) responded (2CR, 9PR) at a median time of 5 months, with a 6‐month probability of renal response of 43%. Five patients (45%) relapsed at a median time of 17 months. DsDNA titres decreased in 69%. Side‐effects were minimal. Conclusions: Single‐dose rituximab is effective in relapsed/refractory lupus nephritis. Longevity of B‐cell depletion with single‐dose rituximab is similar to that of four doses with potentially fewer side‐effects.